Reconfigurations of in-store shopping practices for consumers with disabilities : A mobile shopping view (Gestão & Regionalidade, 2025)
Smartphones have promoted important changes in daily activities. When observing consumers with disabilities, devices have improved their quality of life. Nevertheless, there is still a lack of understanding about how they use smartphones during these in-store shopping activities. This paper aims to understand how the use of smartphones reconfigured consumers with disabilities' in-store shopping practices. We theoretically approach studies on m-shopping, practice theory and disability studies. Methodologically, we conducted virtual focus groups formed by consumers with disabilities in different Brazilian regions, divided into six different groups from May to November 2021. Smartphones in in-store shopping practices interconnects multiple activities and it involves different elements from traditional shopping practices. New perceptions are presented in the use of material, competency, and meaning elements for the performance. Understanding the practices becomes an important lens for comprehending how consumers make their purchases, as a means of reducing vulnerability experienced in their shopping practices.
Keywords: Social Practice Theory; Consumers with Disability; Mobile Shopping